Ethnocultural influences for zoonoses transmission in multi-ethnic communities in Nepal - Bagale, Kosh Bilash; Adhikari, Ramesh; Acharya , Devaraj; Gaire, Basant; Pokhrel, Bidhusi (Journal of Health Promotion, 2021)
Animals contribute to a pivotal role in human societies. Occupational exposure to animals is barred in several ethnicities in Nepal. Limited studies have been found on zoonoses-related diseases and their knowledge, practices, and perception regarding ethnic groups. This study aims to identify the associated factors for human closeness to animals and their host characteristics related to ethnocultural practices. A total of 20 articles were reviewed. In addition to the review, 25 people from different ethnic groups were interviewed. The ethnomedicinal practice and host characteristics of animals for various zoonoses were reviewed from published papers and database journals. There are 1415 species identified as pathogenic to humans, 61% categorized as zoonotic, and of the 175 newly emerging pathogens, 75% are listed as zoonoses. Almost all studies among ethnic groups in Nepal revealed that people interact closely with animals for several reasons, including cultural, religious, and ethnomedical practices. Most of the domesticated animals are also possible hosts for the transmission of zoonoses. So, creating awareness about preventing zoonoses is crucial for the protection of the human race. These findings call for immediate action by government and policymakers to control prevalent zoonoses by commencing proactive activities among at-risk groups.